Molecular mechanisms controlling CFTR gene expression in the airway - Zhang, Zhaolin (Blackwell Publishing Ltd, 2012)
The low levels of CFTR gene expression and paucity of CFTR protein in human airway epithelial cells are not easily reconciled with the pivotal role of the lung in cystic fibrosis pathology. Previous data suggested that the regulatory mechanisms controlling CFTR gene expression might be different in airway epithelium in comparison to intestinal epithelium where CFTR mRNA and protein is much more abundant. Here we examine chromatin structure and modification across the CFTR locus in primary human tracheal (HTE) and bronchial (NHBE) epithelial cells and airway cell lines including 16HBE14o- and Calu3. We identify regions of open chromatin that appear selective for primary airway epithelial cells and show that several of these are enriched for a histone modification (H3K4me1) that is characteristic of enhancers. Consistent with these observations, three of these sites encompass elements that have cooperative enhancer function in reporter gene assays in 16HBE14o- cells. Finally, we use chromosome conformation capture (3C) to examine the three-dimensional structure of nearly 800 kb of chromosome 7 encompassing CFTR and observe long-range interactions between the CFTR promoter and regions far outside the locus in cell types that express high levels of CFTR.